Effect of Fluid Supplementation on the Duration of Phototherapy (Bangladesh Journal of Child Health, 2018)
Background: Hyperbilirubinemia or jaundice is a common condition found in neonates. If intervention is not initiated in case of gradually increasing hyperbilirubinemia may progress to develop kernicterus. Subclinical dehydration (Serum osmolality >290 mosm/kg) due to evaporative losses and poor intake of breast milk can lead to an increased incidence and exaggeration of jaundice in newborns leading to longer duration of phototherapy. Adequate hydration and good urine output improve the efficacy of phototherapy.Objective: To evaluate the effect of fluid supplementation on the duration of phototherapy.Methods: This was a randomized controlled trial conducted in NICU of BSMMU, Dhaka, Bangladesh. Sixty-four term neonates with severe nonhemolytic hyperbilirubinemia (TSB >18 mg/dl to